Skrining retinopati hipertensi di layanan kesehatan primer di Palembang - Ramzi Amin; Petty Purwanita; Riani Erna; Prima Maya Sari; Eka Rahmadini; vidya hestika (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Hypertension is a condition of blood vessels that have high pressure. Hypertensive retinopathy is a complication of hypertension. The prevalence of hypertensive retinopathy varies between 2% -15%. There was lack of data regarding the prevalence of hypertensive retinopathy in Indonesia. Hypertensive retinopathy identification and diagnosis should be performed by an ophthalmologist. Most ophthalmologists are not assigned to primary health care. So that for cases of hypertension that can be resolved at primary health care such as Puskesmas, the true rate of hypertensive retinopathy is unknown. In addition, the patient's lack of awareness about routine eye examinations also causes the prevalence of hypertensive retinopathy to be unknown. This study aims to examine hypertensive retinopathy in hypertensive patients who are attending Puskesmas in Palembang, namely Puskesmas Dempo and Merdeka. The examination was carried out on 150 hypertensive patients. There were 15,3% patients with hypertensive retinopathy of which 10% had a history of hypertension more than 5 years and 5,3% less than 5 years. It could be argued that there are patients with hypertensive retinopathy who were undiagnosed in the community. The role of the Puskesmas in referring patients with hypertension to an ophthalmologist is very important so that the cases of hypertensive retinopathy could be detected immediately.